Analysis of the assortment structure of antidepressants on the domestic pharmaceutical market: antidepressive agents, depression, marketing, mental health, COVID-19 - Chorniy , Sofiia; Bilyk , Yaroslav; Pavliuk , Bohdana; Stechyshyn , Iryna (The Ukrainian Scientific Medical Youth Journal, 2023)
а feature of the course of diseases, the correction of which requires the use of antidepressants, is the small number of requests for specialized help in the early stages of the development of mental disorders. This creates certain limitations for fast and effective therapy. However, given that depression is the most common mental disorder in the world, there is a certain scientific interest in researching this pathology. The purpose of the work is a comprehensive assortment analysis of the group N06A "Antidepressants" on the pharmaceutical market of Ukraine. The study of the assortment of antidepressants registered on the pharmaceutical market was carried out in accordance with the Anatomical-Therapeutic-Chemical classification and the data of the State Register of Drugs of Ukraine. The objects of research were information on drugs registered in Ukraine, which belong to category N06A "Antidepressants". According to the data of the State Register of Drugs of Ukraine, as of January 2022, taking into account drugs produced in different dosages, 149 trade names of drugs belonging to category N06A "Antidepressants" and represented by 20 international non-proprietary names were registered. Of all the antidepressants registered on the pharmaceutical market of Ukraine, 52 drugs with a limited validity period of the registration certificate should be noted. The pharmaceutical market of Ukraine for the treatment of depression is clearly dominated by foreign pharmaceutical companies, and the share of domestic companies is represented only by 18.1%, which indicates the need to expand this group of drugs, because 9 out of 20 international non-proprietary names do not have a single domestic drug. Antidepressants are imported to the Ukrainian pharmaceutical market from 19 countries. The main importing countries are: India – 18.9%, Slovenia – 12.3%, Germany – 9.0%, Poland and Turkey – 7.4% each, Hungary – 5.7%. Other countries collectively occupy 39.3% of the pharmaceutical market of imported drugs from category N06A "Antidepressants". But it is important that according to the Anatomical-Therapeutic-Chemical classification, in Ukraine this group of drugs is classified only into 3 subgroups. It should be noted that in Ukraine there are harmonized protocols, where, according to the recommendations for the treatment of depression, drugs are offered that, unfortunately, are not registered on the domestic market, which is reflected in the absence of two subgroups: N06AF and N06AG, which creates certain problems of patient access to high-quality and effective therapy recommended by the 2020 "Protocols for the diagnosis and treatment of patients with mental disorders (Finnish version)".